2019
DOI: 10.1186/s41065-019-0115-7
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of the germline mutation BRCA1: p.Ile1845fs in a large cohort of Han Chinese breast cancer

Abstract: BackgroundBreast cancer is a one of the malignant carcinomas partially caused by genetic risk factors. Germline BRCA1 gene mutations are reportedly associated with breast cancers. Identification of BRCA1 mutations greatly improves the preventive strategies and management of breast cancer. The aim of our study was to investigate the frequency of the deleterious BRCA1: p.Ile1845fs variant in breast carcinomas, as well as the correlation between p.Ile1845fs variant with clinicopathological parameters and clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…This implies a substantial amount of diversity harbored by the trees investigated and that the four genetic clusters were significantly distinct. The level of population differentiation (F ST ) observed in this study was higher than the values reported by Juma et al [ 25 ] for the same plant material when AMOVA was carried out on district-based populations (F ST = 0.061, p < 0.0001) and altitudinal groups (F ST = 0.025, p < 0.0001). Gross-German and Viruel [ 37 ] and Boza et al [ 4 ] found an overall population differentiation of 0.25 and 0.193, respectively, which are comparatively higher than the value obtained in our study.…”
Section: Discussioncontrasting
confidence: 86%
See 4 more Smart Citations
“…This implies a substantial amount of diversity harbored by the trees investigated and that the four genetic clusters were significantly distinct. The level of population differentiation (F ST ) observed in this study was higher than the values reported by Juma et al [ 25 ] for the same plant material when AMOVA was carried out on district-based populations (F ST = 0.061, p < 0.0001) and altitudinal groups (F ST = 0.025, p < 0.0001). Gross-German and Viruel [ 37 ] and Boza et al [ 4 ] found an overall population differentiation of 0.25 and 0.193, respectively, which are comparatively higher than the value obtained in our study.…”
Section: Discussioncontrasting
confidence: 86%
“…Some genetic markers that have been applied are isozymes [ 16 ], minisatellites [ 17 ], variable number tandem repeats (VNTRs) [ 18 ], randomly amplified polymorphic DNA (RAPD) [ 19 ], and restriction fragment length polymorphisms (RFLP) [ 20 , 21 ]. Others are inter-simple sequence repeats (ISSR) [ 22 ], simple sequence repeat (SSR) [ 15 , 23 , 24 , 25 ], and single nucleotide polymorphisms (SNPs) [ 5 , 26 , 27 ]. Choosing which marker type to employ in a diversity study depends on the study objectives and available financial resources, expertise, and facilities [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations